FINANCIAL INDEPENDENCEOF THE MUNICIPALITIES IN BULGARIA – STATE AND DEVELOPMENT - Ivanova, Diyana (E-Journal VFU, 2024)
The analysis of the financial condition of budgetary organizations provides opportunities for developing managerial decisions aimed at creating conditions for good financial management of public finances. The current paper studies the financial independence of the municipalities in Bulgaria and examines the trends in its development. On this basis, it draws guidelines for optimizing this aspect of the financial situation of the municipalities.
Keywords: financial independence; local self-government; public sector